PENGARUH BERKUMUR SARI BUAH ANGGUR MERAH BERBAGAI KONSENTRASI DAN CHLORHEXIDINE 0,12% TERHADAP INDEKS PLAK - Henny Henny Eka Putri; Prima Agusmawanti; Ade Ismail (Faculty of Dentistry, Universitas Islam Sultan Agung, 2014)
Background: Plaque plays an important role in causing caries and periodontal problems. Plaque control should be done chemically in an effort to reduce the accumulation of plaque in the oral cavity. Juice of red grapes (Vitis vinifera) has a chemical compound as an antibacterial catechins and tannins . The purpose of this study is to determine the effect of rinsing with red grape juice with different concentrations of chlorhexidine and 0.12 % during the 7 day study of the reduction of plaque index. Method: This study is quasi-experimental study which was conducted on 25 students Aisyiyah Orphanage. After Scaling and toothbrush cleaning, each sample rinsed with 10 ml of solution 3 times a day has been accepted in accordance with the treatment without taking action toothbrush for 7 days. Result: The mean plaque index in the treatment group began to experience a gradual decline in the fourth day until the seventh day of the study. From the results of Mann Whitney test analysis found significant differences between the various groups of SBA and chlorhexidine 0.12 % concentration with distilled water on the fourth to the seventh day of the study. But betweenthe SBA 100 % with chlorhexidine 0.12 % there is no significant difference. Conclusion: This can be concluded that rinsing with red grape juice with a concentration of 50 % , 75 % 100 % and chlorhexidine 0.12 % has efficacy in reducing the plaque index. 100 % SBA group is a group of the most effective concentration.